2016
DOI: 10.1007/s11999-015-4494-4
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated Perioperative Hip Fracture Comanagement Programs are Cost-effective in High-volume Centers: An Economic Analysis

Abstract: Background Osteoporotic hip fractures are common injuries typically occurring in patients who are older and medically frail. Studies have suggested that creation of a multidisciplinary team including orthopaedic surgeons, internal medicine physicians, social workers, and specialized physical therapists, to comanage these patients can decrease complication rates, improve time to surgery, and reduce hospital length of stay; however, they have yet to achieve widespread implementation, partly owing to concerns reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 58 publications
(118 reference statements)
3
49
0
2
Order By: Relevance
“…Previous reports estimate that hospital care represents 44% of the direct costs associated with hip fractures, 22 with average inpatient hospitalization costs an estimated US$699/day. 28 It is reasonable to assume that by reducing inpatient LOS by 1.6 days, we have significantly reduced inpatient cost of hip fracture care at our hospital. Admitting patients to a primary orthopedic service has also streamlined postoperative referrals to our outpatient fracture liaison service for management of bone health and prevention of fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports estimate that hospital care represents 44% of the direct costs associated with hip fractures, 22 with average inpatient hospitalization costs an estimated US$699/day. 28 It is reasonable to assume that by reducing inpatient LOS by 1.6 days, we have significantly reduced inpatient cost of hip fracture care at our hospital. Admitting patients to a primary orthopedic service has also streamlined postoperative referrals to our outpatient fracture liaison service for management of bone health and prevention of fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although the downstream financial savings associated with early initiation of osteoporosis treatment is unclear, it is reasonable to assume that we can help prevent additional fragility fractures with early intervention. 28 …”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that an intensive and early geriatric intervention reduces mortality and the number of clinical complications, but did not find a significant effect on the LOS. From an economic perspective, it seems that collaborative models can be cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…Je nach Studie konnten eine Reduktion der Mortalität und der Komplikationen und eine Verbesserung funktioneller Parameter verglichen mit der Standardtherapie erzielt werden [9,10]. In Zentren ist die integrative unfallchirurgischgeriatrische Behandlung proximaler Femurfrakturen daher auch kosteneffektiver und wirtschaftlicher als die Standardbehandlung durch eine Disziplin allein [10,11]. Auch wenn die bisherigen Studien alle zu proximalen Femurfrakturen durchgeführt wurden, ist zu vermuten, dass auch geriatrische Patienten mit anderen Verletzungen von einer unfallchirurgisch-geriatrischen Zusammenarbeit profitieren.…”
Section: Merkeunclassified